Derivation of a cinematic formula

  • #1
sitzpillow
4
0
I'm really happy about every hint!

Homework Statement


There is a ball on hight h which is dropped on a table.
With every Impact the ball loses velocity v by a factor a<1.
I Need to Show the following:
The time T after the ball stopps bouncing is:
[tex] T = \frac{1+a}{1-a} (\frac{2h}{g})^\frac{1}{2} [/tex]

There is a hint to start to calculate the time t_k between the takeoff and the next Impact
and that I should use the geometric series.
We don't need to think about air resistance.

2. The attempt at a solution
My Problem is that if I calculate t_k, I don't include the first time t_0 when the ball gets dropped.
[tex] t_k = 2\frac{h_k}{v_k}=2\frac{h_k}{a^k v_0}=a^{-k} (\frac{2h_k}{\sqrt{(2 h_0 g)}}) = a^{-k} (\sqrt{(\frac{4h_k^2}{2 h_0 g}}) [/tex]
with [tex] v=\sqrt{2gh}[/tex] which I got from E_pot=E_kin.
But now I can't shorten h_0 with h_k and a^-k <1 so I can't use the geometric series?!
Is it wrong to use v=s/t ⇔t=s/v since we have a accelarated movement.
 
Physics news on Phys.org
  • #2
Yes its wrong to use that. You should take instead [itex]t_k=2\frac{v_k}{g}, k\geq 1[/itex], [itex]t_0=\sqrt\frac{2h}{g}[/itex].
 
Last edited:
  • #3
How does the v_k looks like?
[itex] t_k=2 \frac{a^k v_0}{g} = 2 a^k \frac{\sqrt{2gh}}{g}= 2 a^k \sqrt{\frac{2h}{g}} [/itex] ?
What's next?
 
  • #4
Next is geometric series of ##t_k##. ##T=t_0+\sum\limits_{k=1}^{\infty}t_k=\sqrt\frac{2h}{g}+\sum\limits_{k=1}^{\infty}t_k##. Notice that the actual ##t_0## is half of what you get from the formula of ##t_k## for k=0(because we drop the ball from above the table), that's why i put it outside the summation which summation is done from k=1 for this reason.

or you can do the series from k=0 but then subtract ##\sqrt\frac{2h}{g}##.
 
Last edited:
  • #5
Thank you. To finish that threat I conclude:

t_k means the time between the k and k+1 impact.

for t_0
we get
[tex]t_0=\sqrt{\frac{2h}{g}}[/tex] with [tex]s=ut+\frac{1}{2}gt^2[/tex]

for t_k with k>0
[tex]\Sigma{t_k}=\Sigma_1^n{2 \frac{a^k v_0}{g}}=\Sigma_0^n{2 \frac{a^k v_0}{g}}-\frac{2v_0}{g}[/tex]
now we let n go to infinity and use the geometric series:
[tex]\Sigma_{n=0}^{\infty}{t_k}=\Sigma_{n=0}^{\infty}{2 \frac{a^k v_0}{g}}-\frac{2v_0}{g}=2\frac{v_0}{g}(\frac{1}{1-a}-1)=\frac{v_0}{g}\frac{2a}{1-a}=\sqrt{\frac{2h}{g}}\frac{2a}{1-a}[/tex]
by using [tex]E_{kin}=E_{pot}[/tex]

Adding 1. plus 2. we get: [tex]\sqrt{\frac{2h}{g}}\frac{1+a}{1-a}[/tex]
 
  • #6
There is a slightly easier way.
Consider the ball starting by rising from the ground at speed v. The time to first bounce is 2v/g. If the time to coming to rest is t(v) then t(v) = 2v/g + t(av). Guess a linear solution, t(v) = kv, and find that ##k=\frac{2}{g(1-a)}##. Then it is a matter of converting to the given initial conditions.
 
Back
Top